Securing sensor data transmission with ethernet elliptic curve cryptography secure socket layer on STM32F103 device - Seniman Seniman; Baihaqi Siregar; Rani Masyithah Pelle; Fahmi Fahmi (Institute of Advanced Engineering and Science, 2021)
Currently there is no method, feature, or ability in securing data transmission in microcontroller systems and applications with client-server scheme communication, while major modern computer systems using secure socket layer (SSL) for establishing secure communication. However, ESP espressif based microcontroller has supported SSL communication to secure data transmission, but only works on the Wi-Fi network. A single-board computer based embedded system has fully supported SSL communication, but it costs a very high price. On the other hand, STM32F103 microcontrollers with a very affordable price even cheaper than the Arduino board has the opportunity to build secure data communication using SSL protocol based on MbedTLS library. In addition to wiznet W5100/W5500 ethernet shield, an STM32F103 SSL client device has been successfully built in this study. The SSL client device supports ECDHE ECDHA AES128 CBC SHA256 SSL cipher suite. The Apache web server must also be configured to support this cipher suite by generating OpenSSL ECC (elliptic curve cryptography) certificate. The system was tested with the LM35 analog temperature sensor, and as a result, the STM32F103 SSL client has successfully secured the data transmission to the Apache SSL web server. The communication time was 3 seconds for the first connection and 42 ms for the next data transmission.